(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
This paper discusses the stages of linguistic historiography leading from the genealogical tree, where the linguistic change is conceived as a one-dimensional event (i.e., change through time), to the geolinguistic approach, providing a two-dimensional image (i.e, change thorugh time and space), and eventually to sociolinguistics, which represents the linguistic change according to a three-layer scheme (time, space and diastratic level of speakers). It is shown that the geolinguistic two-dimensional approach is not able to provide chronological clues. Moreover, some tendencies are taken into account, resulting from the matching of the outputs of linguistic change with the system where it takes place. Finally, the paper attempts to distinguish those changes due to irradiation from those ensuing from polygenesis. KEYWORDS: language change, history of linguistics, geolinguistics, sociolinguistics, chronology